Clinical utility of eco-color-power Doppler ultrasonography and contrast enhanced magnetic resonance imaging for interpretation and quantification of joint synovitis: a review - Carotti, Marina; Galeazzi, Vittoria; Catucci, Francesca; Zappia, Marcello; Arrigoni, Francesco; Barile, Antonio; Giovagnoni, Andrea (Acta Biomedica Atenei Parmensis, 2018)
With the introduction of new biologics such as anti-TNF-alpha antibodies and other therapies in the treatment of inflammatory arthritis, capable of halting joint destruction and functional disability, there are new pressures on diagnostic and prognostic imaging. Early demonstration of pre-erosive inflammatory features and monitoring of the long-term effects of treatment are becoming increasingly important. Early detection of synovitis offers advantages in terms of allowing early instigation of therapy and may allow the identification of those patients displaying more aggressive disease who might benefit from early intervention with expensive DMARD therapy. Advanced imaging techniques such as ultrasound (US) and magnetic resonance imaging (MRI) have focussed on the demonstration and quantification of synovitis and allow early diagnosis of inflammatory arthropathies such as rheumatoid arthritis (RA) and psoriatic arthritis (PsA). Synovitis represents a potential surrogate measure of disease activity that can be monitored using either MRI or US; the techniques have, generally, focused on monitoring synovial volume or quality as assessed by its vascularity. However to achieve these goals, standardisation and validation of US and MRI are required to ensure accurate diagnosis, reproducibility and reliability. Each modality has different strengths and weaknesses and levels of validation. This article aims to increase the awareness of radiologists and rheumatologists about this field and to encourage them to participate and contribute to the ongoing development of these modalities. Without this collaboration, it is unlikely that these modalities will reach their full potential in the field of rheumatological imaging. This review is in two parts. The first part addresses the role of US and colour or power Doppler sonography (PDUS) in the detection and monitoring of synovitis in inflammatory arthropathies. The second part will look at advanced MR imaging and Dynamic contrast-enhanced MRI techniques and in particular how they are applied to the monitoring of the disease process.